Macrocyclic Protease Inhibitors with Reduced Peptide Character1. (5th June 2014) - Chua, Krystle C. H.; Pietsch, Markus; Zhang, Xiaozhou; Hautmann, Stephanie; Chan, Hon Y.; Bruning, John B.; Gütschow, Michael; Abell, Andrew D.
Abstract There is a real need for simple structures that define a β‐strand conformation, a secondary structure that is central to peptide–protein interactions. For example, protease substrates and inhibitors almost universally adopt this geometry on active site binding. A planar pyrrole is used to replace two amino acids of a peptide backbone to generate a simple macrocycle that retains the required geometry for active site binding. The resulting β‐strand templates have reduced peptide character and provide potent protease inhibitors with the attachment of an appropriate amino aldehyde to the C‐terminus. Picomolar inhibitors of cathepsin L and S are reported and the mode of binding of one example to the model protease chymotrypsin is defined by X‐ray crystallography.